Synthesis of cesium lead halide perovskite/zinc oxide (CsPbX3/ZnO, X= Br, I) as heterostructure photocatalyst with improved activity for heavy metal degradation - Gull, Sehrish; Batool, Saima; Li, Guijun; Idrees, Muhammad (Frontiers in Chemistry, 2022)
Inorganic perovskites have been recognized as highly potent materials for the dispaly and medical industries due to their outstanding features. However, there haven’t been many reports on their implications as a photocatalyst for the removal of heavy metals. Photocatalysis has been regarded as a significant approach for the removal of pollutants because of its great sustainability, improved efficiency, and reduced energy consumption. Here, we applied inorganic cesium lead halides (Br and I) with zinc oxide heterojunction as a photocatalyst for the first time. The heterostructure has been synthesized by the traditional hot injection strategy and its photocatalytic activity was systematically investigated. Interestingly, the CsPbX3/ZnO heterostructure as a photocatalyst has a homogeneous geometry and possesses an excellent degradation efficiency of over 50% under xenon UV-Visible light. The CsPbX3/ZnO catalyst carries superior oxidation/reduction properties and ionic conductivity due to the synergistic photogenerated charge carrier and interaction between CsPbX3 and ZnO. The recycling experiment showed the good stability of the catalysts. These findings suggest that inorganic lead halide heterostructure has the potential to be used for heavy metal degradation and water pollution removal catalysts.